QIRABOX: Quran Murottal Speaker with Speech Recognition Based on Internet of Things - Rimadana, Heny (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
This research aims to design and implement an IoT-based speaker control system for Quran Murottal using voice commands, specifically targeting visually impaired individuals. The system utilizes speech recognition technology to overcome the challenges that visually impaired users face when controlling devices through buttons or remotes. The Android application "Qirabox" integrates Google Speech Recognition to convert voice commands into text, which is then processed by the Aho-Corasick algorithm for pattern matching. The system uses the MQTT protocol for IoT communication, with an ESP32 microcontroller and an IR Transmitter to send infrared signals to control the speaker. The system was evaluated through 50 trials with 10 visually impaired participants at PERTUNI Malang, resulting in a low error rate of 2%. Furthermore, the System Usability Scale (SUS) evaluation provided a score of 78.75 (Good), indicating the system"™s usability and effectiveness in meeting user needs. This research demonstrates the potential of voice-controlled speaker systems and contributes to the development of assistive technology for visually impaired individuals, offering a significant improvement in accessibility and ease of use.